1996
DOI: 10.3109/10428199609051759
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Effects of G-CSF and GM-CSF on Cell Growth and Ara-C Cytotoxicity in Childhood Leukemias Which Express Myeloid Markers

Abstract: It is uncertain if acute lymphoblastic leukemia (ALL) cells expressing myeloid makers can respond to granulocyte colony-stimulating factor (G-CSF) and granulocyte macrophage colony-stimulating factor (GM-CSF). We investigated the effects of G-CSF (0.01 microgram/ml) and GM-CSF (0.01 microgram/ml) on [3H]thymidine (TdR) uptake, and the cytotoxicity of 1-beta-D-arabinofuranosylcytosine (ara-C) in leukemia cells from 17 pediatric patients. ALL cells without myeloid markers did not respond to G-CSF or GM-CSF. On t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…There are several reports, however, implying that some B-or T-cell leukaemias, biphenotypic leukemia cells, or leukaemic cells with specific translocations may express G-CSF receptors and are able to respond to exogenous G-CSF [23,24,[26][27][28]. In the present work we studied how G-CSF in cell suspension influences the drug sensitivity of KG-1 leukaemic cells.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…There are several reports, however, implying that some B-or T-cell leukaemias, biphenotypic leukemia cells, or leukaemic cells with specific translocations may express G-CSF receptors and are able to respond to exogenous G-CSF [23,24,[26][27][28]. In the present work we studied how G-CSF in cell suspension influences the drug sensitivity of KG-1 leukaemic cells.…”
Section: Discussionmentioning
confidence: 91%
“…Oh et al observed that G-CSF receptor expression was increased in relapsed or refractory ALL and a significant correlation between G-CSFR and GM-CSFR expression was found [32]. Based on the above studies the question arises whether G-CSF used as a component of supportive treatment of childhood ALL with febrile neutropenia can lead to proliferation of not only the normal myeloid cells but of lymphoid leukaemic blasts, that coexpress myeloid markers as well [28]. In addition, whether or not G-CSF influences drug sensitivity of blast cells remains to be answered, too.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…There are a few reports that some ALL cells express G-CSF and GM-CSF receptors and/or respond to these myelopoietic cytokines (Drach et al 1994;Freedman et al 1993;Higashigawa et al 1996;Komada et al 1993;Ohno 1994;Shimoda et al 1992;Shinjo et al 1997). Other studies, however, failed to confirm the presence of receptors to myelopoietic cytokines on ALL cells (Park et al 1989;Piao and Okabe 1990;Tomeczkowski et al 1995).…”
Section: Introductionmentioning
confidence: 89%